2022
DOI: 10.1371/journal.pntd.0010566
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus persistence in the male macaque reproductive tract

Abstract: Zika virus (ZIKV) is unique among mosquito-borne flaviviruses in that it is also vertically and sexually transmitted by humans. The male reproductive tract is thought to be a ZIKV reservoir; however, the reported magnitude and duration of viral persistence in male genital tissues vary widely in humans and non-human primate models. ZIKV tissue and cellular tropism and potential effects on male fertility also remain unclear. The objective of this study was to resolve these questions by analyzing archived genital… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Due to their immaturity, the testes of young KO A129 mice showed greater tissue damage than those of adult animals [ 60 ], in which no atrophy, inflammation, or hemorrhage was observed. Similar findings were described in a study of 51 NHPs ( Macaca mulatta and Macaca fascicularis ) from a rather heterogeneous sample group, in which higher rates of ZIKV RNA detection and histopathological lesions were observed in mature primates than sexually immature primates; however, these findings were observed more in the epididymis, prostate, and seminal vesicles than the testes, which were not available or samples were excluded [ 14 ]. In contrast to the aforementioned research, in our study, it was possible to observe histopathological damage and to detect ZIKV RNA in pubertal animals.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Due to their immaturity, the testes of young KO A129 mice showed greater tissue damage than those of adult animals [ 60 ], in which no atrophy, inflammation, or hemorrhage was observed. Similar findings were described in a study of 51 NHPs ( Macaca mulatta and Macaca fascicularis ) from a rather heterogeneous sample group, in which higher rates of ZIKV RNA detection and histopathological lesions were observed in mature primates than sexually immature primates; however, these findings were observed more in the epididymis, prostate, and seminal vesicles than the testes, which were not available or samples were excluded [ 14 ]. In contrast to the aforementioned research, in our study, it was possible to observe histopathological damage and to detect ZIKV RNA in pubertal animals.…”
Section: Discussionsupporting
confidence: 84%
“…An analysis of the kinetics of infection, with evidence of fever ( Figure 2 A), viremia ( Figure 2 B), and IgM antibody detection ( Figure 2 C). Thus, it was possible to delineate the acute phase of infection (between 1 and 10 dpi) and the onset of the convalescent phase (10 dpi to 21 dpi), periods that are similar to those in other research with NHPs as well as humans [ 14 , 78 ]. Interestingly, animal AT-005 showed a persistent febrile state between 3 and 10 dpi, which was observed to be consistent with the viremic period (3 to 10 dpi), and a higher O.D.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Using animal and cell culture models, components of the male reproductive tract shown to be a site of long-term replication and inflammation include the epididymides [14][15][16] , the prostate [17][18] , and the testes [19][20][21] , leading to reduced fertility in mouse models 21 . Studies using ZIKV-infected NHP 22 and mouse models [20][21] have also showed ZIKV infection can lead to histopathologic lesions in the testes, which is a health concern for infected men in addition to impacting fertility. The testes are the site of spermatogenesis and may play a key role in ZIKV-caused infertility as well as viral maintenance for sexual transmission.…”
Section: Introductionmentioning
confidence: 99%